MASYARAKAT PASSING OVER DALAM BERAGAMA: PERWUJUDAN CIVIL SOCIETY MASYARAKAT MUSLIM-KRISTEN MADURA DI SUMBERPAKEM JEMBER - Asy’ari (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
Moving away and sterilizing religion from acts of violence by some of its fol-lowers is an overwhelming task for clerics and more so for the leaders and religious leaders of this era of globalization. Bad is indeed linking religion, especially Islam, with acts or violent behavior perpetrated by some adher-ents. However, the reality of daily life speaks differently. Attitudes and acts of violence committed in various countries often carry religion. Basically, this paper is about to decipher a reality in a village that is Sumberpakem, a village located under the slope of Mount Raung, Sumberjambe District-Jember-East Java, which nature comes as the antithesis that religion and its set of elements are responsible for violent conflict. The author tries to des-cribe this research through the study approach of passing over in the social context so that the study can really be felt at the grass roots so that peace becomes a witness (shahada) as well as can be witnessed together for the rea-lization of civilized society.